1998
DOI: 10.1108/03068299810214089
|View full text |Cite
|
Sign up to set email alerts
|

Foundation of business ethics in contemporary religious thought: the Ten Commandment perspective

Abstract: Perhaps, one of the most influencing set of principles in Christianity, Judaism and Islam is the Ten Commandments (TCs). They are often recited by ordinary and élite people of these three major faiths. In fact, in some quarters among Christians, Jews and Muslims, the TCs are taken for granted and their influence is reflected in the behavior and attitudes of the believers. The widespread use of the TCs and their popularity can be attributed to their practical application to day-to-day relationships and to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 5 publications
1
29
0
Order By: Relevance
“…We begin with several examples of the former. Ali & Gibbs (1998) relate the Ten Commandments of three major religions (Judaism, Christianity, and Islam) to the work ethics and practices of their believers. They argue that in a global marketplace and economy, with diversity as the norm rather than the exception, leaders and managers can benefit from understanding the basic embedded religious drives that members of these three religions may bring to their work environment.…”
Section: Tied To Religionmentioning
confidence: 99%
“…We begin with several examples of the former. Ali & Gibbs (1998) relate the Ten Commandments of three major religions (Judaism, Christianity, and Islam) to the work ethics and practices of their believers. They argue that in a global marketplace and economy, with diversity as the norm rather than the exception, leaders and managers can benefit from understanding the basic embedded religious drives that members of these three religions may bring to their work environment.…”
Section: Tied To Religionmentioning
confidence: 99%
“…All business decisions must be guided by iman, which practically means abiding by the shariah law, engaging in the things that are permitted (halal), avoiding those thatare forbidden (haram) (Alawneh, 1998). Business decision makers are free to make choices, but religious principles provide a framework for the appropriate exercise of that choice (Ali & Gibbs, 1998 …”
Section: Islamic Management Practices Authorsmentioning
confidence: 99%
“…REL at workplace has been a point of concern in numerous studies that reviewed the linkage between faith and work (Graafland, Mazereeuw, & Yahia, 2006;Lynn, Naughton, & VanderVeen, 2009;Steele & Bullock, 2009;Pio & Syed, 2014). Many others (e.g., Furnham & Muhiudeen, 1984;Ali & Gibbs, 1998;Niles, 1999) suggested relying on commonality of values in all religions. US Equal Employment Opportunity Commission (2011) indicated that employee REL at American workplace has been one of the most demanding and controversial issues.…”
Section: Religiositymentioning
confidence: 98%